Oral Squamous Cell Carcinoma: The Molecular Characteristics - Syafruddin Ilyas (Talenta Publisher, 2022)
Oral squamous cell carcinoma (OSCC) is a malignancy that occurs on keratinocyte cells that have the potential to spread through lymphatic tissue or blood vessels. These carcinomas develop as a result of a series of molecular factors, which are influenced by individual genetic factors as well as environmental exposure to carcinogens. The evaluation of the prognosis and treatment plan for OSCC are mainly based on the clinical picture of the tumor or the TNM classification (T, tumor; N, lymph nodes or glands; M, metastases). The disadvantage of this diagnostic technique is that it does not consider the biological properties of the tumor, molecular characteristics, or tumor location, so it is deemed incapable of predicting patient safety. The purpose of this paper is to provide an overview of the etiology, pathogenesis, clinical picture, radiographic findings, and histopathological features of OSCC to help those concerned make the correct diagnosis. We use references from the last ten years article to obtain an up-to-date data. Based on our literacy study, we discovered that the presence of pseudoepitheliomatous hyperplasia (PEH) and keratoacanthoma distinguishes OSCC from many other oral cavity carcinomas (CA). The amount of P53 expression in tissues experiencing PEH and CA, as well as the integration of several other pro-cancer protein expressions, can be used to detect severity early. We can conclude that early detection of OSCC should be done by assessing the expression of proteins that cause the severity of cancerous lesions so that suppression of these cancer-inducing proteins can be treated while the levels are still low